Cell Permeable Peptides: A Promising Tool to Deliver Neuroprotective Agents in the Brain - Tiziana Borsello; Xanthi Antoniou (MDPI AG, 2010)
The inability of most drugs to cross the blood-brain barrier and/or plasma membrane limits their use for biomedical applications in the brain. Cell Permeable Peptides (CPPs) overcome this problem and are effective in vivo, crossing the plasma membrane and the blood-brain barrier. CPPs deliver a wide variety of compounds intracellularly in an active form. In fact, many bioactive cargoes have neuroprotective properties, and due to their ability to block protein-protein interactions, offer exciting perspectives in the clinical setting. In this review we give an overview of the Cell Permeable Peptides strategy to deliver neuroprotectants against neurodegeneration in the CNS.